2021
DOI: 10.1590/1519-6984.227200
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cadmium tolerance and biosorptive potential of Bacillus Cereus GCFSD01 isolated from cadmium contaminated soil

Abstract: Continuous occurrence of heavy metals is a major cause of environmental pollution due to its toxic effects. At minimum concentrations, these metals are highly reactive and can gather in the food chains and food web, causing major dangers to public health concerns. Soil samples were collected from Paharang drain, Faisalabad. Cadmium tolerant bacteria were isolated and evaluated for their MIC against Cd. The isolated bacterial strain GCFSD01 showed MIC value upto 30 mM/L. The bacterial strain with the highest re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…putida strain 06909. Muzammil et al (2021) also isolated cadmium resistant bacteria (Bacillus cereus GCFSD01) from Paharang drain. Morphological and biochemical characteristics showed the ZSB13 was gram negative, rod shaped and non-spore forming bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…putida strain 06909. Muzammil et al (2021) also isolated cadmium resistant bacteria (Bacillus cereus GCFSD01) from Paharang drain. Morphological and biochemical characteristics showed the ZSB13 was gram negative, rod shaped and non-spore forming bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Suggesting that heavy metal biosorption seems to be more affected by larger temperature ranges. In contrast Muzammil et al, (2021) found that between 25, 37 and 42°C, maximum removal capacity was reached at 37°C [45]. Therefore, for this study temperatures were maintained at 37°C to obtain good growth and heavy metal uptakes.…”
Section: Discussionmentioning
confidence: 90%
“…Bacillus was detected in the metagenome of discarded face masks from landfills, as determined by NGS analysis results about one of the most abundant genera in our samples. Bacillus, which can bind heavy metals to the cell surfaces and provide bioremediation, was also responsible for degrading disposable face mask materials (Muzammil et al, 2021). Bacillus from various locations has been demonstrated to be an effective azo dye degrader (Guembri et al, 2021); plastic degrader (Fibriarti et al, 2021); and organometallic degrader (Tripathi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%